Assessment of the level of economic security of the dairy industry of Ukraine - Korchevska, L.A.; Chukurna, O.P. (BUKETOV BUSINESS REVIEW, 2023)
Object: The aim of the study is to assess the level of economic security of the Ukrainian dairy industry in order to identify threats in a timely manner. The object of the research is the economic security of the dairy industry in Ukraine. The subject of the research is the process of assessing the level of economic security of the dairy industry in Ukraine. Methods: statistical and comparative analysis, taxonomic method and golden section method. Findings: The article builds a fractal model of economic security levels. The resource, commercial and social components are allocated to assess the economic security of the supersystem of the enterprise, namely, the dairy industry of Ukraine. To assess the economic security of the supersystem of the enterprise, namely, the dairy industry of Ukraine, it is proposed to single out the resource, commercial and social components. The stages of the methodology for assessing the level of economic security of the dairy industry in Ukraine, as well as its ranges, are determined. Trends and external threats can be identified on the basis of an assessment, which will allow the enterprise to adapt and develop appropriate measures. Conclusions: The scientific and methodological approach to assessing the level of economic security of the dairy industry in Ukraine has been improved. It is calculated using the method of taxonomic analysis by a posteriori parameters within the individual components (resource, commercial, social). It was stated that there is practically no inflow of investments into the country, and further reduction threatens domestic demand. All this actualizes the solution of the problem of ensuring food security not only at the industry level, but also at the country level. It also requires the development of mechanisms to support agriculture and domestic producers. It has been determined that for the economic security of an enterprise, the supersystem is the economic security of the industry and the country as systems of a higher rank. They go their own way of development and are its external determinants. After all, in a country and industry with a low level of economic security, even a successful (at the beginning) enterprise will face bankruptcy if nothing changes in the surrounding meso- and macro-environment.